English criticism in Japan : essays by younger Japanese scholars on English and American literature - Miner, Earl, 1927-2004; Miner, Earl, 1927-2004; Miner, Earl, 1927-2004 (Princeton legacy library., 1972)
The essays that follow can best be examined without an officious guide. In spite of the international character of Japanese scholarship and criticism of English and American literature, the essays collected here take root in an educational heritage markedly different from that familiar to the personal experience of any but a Japanese reader. Japanese scholars are part of the international fraternity of students of literature in English, and they share methods of study with colleagues in New York or London. Japan has its own literary traditions extending over the centuries. The first major critical essay on Japanese literature, the preface to the first of the imperial anthologies, the Kokinshu, dates from ca. A.D. 905. Without question, Japanese scholars or critics of English and American literature have a special vantage point. Their special view reflects in part their Japanese heritage and in part the special situation of Japan among the nations today. Readers can confidently expect essays interesting for what they tell of familiar authors and works, and that only thereafter will readers reflect that the critic who has heightened said appreciation lives in Japan.